The Link Between Domestic Violence and Abuse and Animal Cruelty in the Intimate Relationships of People of Diverse Genders and/or Sexualities: A Binational Study - Riggs, Damien W. (Journal of interpersonal violence, 2021)
Over the past three decades, a growing body of research has focused on experiences of domestic violence and abuse (DVA) among people of diverse genders and/or sexualities. Missing, however, has been a focus on what is known as “the link” between DVA and animal cruelty with regard to people of diverse genders and/or sexualities. The present article reports on a study of 503 people living in either Australia or the United Kingdom, who reported on both their intimate human relationships and their relationships with animals, including relationships that were abusive. In terms of “the link,” a fifth of respondents who had experienced violence or abuse also reported that animal cruelty had been perpetuated by the violent or abusive partner. Statistical interactions were found between having witnessed animal cruelty perpetrated by a partner, gender and sexuality, and both psychological distress and social connectedness. Female participants who had witnessed animal cruelty reported greater psychological distress and lower levels of social support, and both lesbian and bisexual participants who had witnessed animal cruelty reported lower levels of social support. The article concludes by considering the implications of these findings for future research and service provision.